A Plague of Their Own: Injury Incidence Remains Elevated in the 2021 Major League Baseball Season Compared to Pre-COVID-19 Seasons - Brooks N Platt; Breanna M Sullivan; Shawn Dripchak; Timothy L Uhl; Aaron D Sciascia; William Kibler; Austin V Stone (International Journal of Sports Physical Therapy)
# Background